The Octupole Correlations In The 209bi,209pb Nuclei - Doma, S.B.; salman, Hasan; tfiha, amir darwish (Latakia University Journal -Basic Sciences Series, 2019)
حلت مسألة هارتري-فوك-بوغليوبوف للأنوية التي لها عدد كتلي A=209 باستخدام مبدأ التغير. وتم حساب ارتباط ثماني قطب للإنتقالين ، للنواة 209 Bi من أجل سعات مختلفة لاهتزاز ثماني القطب. وأخيراً حسبنا ارتباط ثماني قطب للإنتقال للنواة Pb209. The self consistent Hartree-Fock-Bogoliubov problem for nuclei with A=209 is solved by using the variation principle. Accordingly, the octupole coupling of and of the nucleus 209Bi have been calculated for different octupole strengths. Moreover, the octupole coupling between of the nucleus 209Pb has been also calculated.